STUDENTS’ ANXIETY AND THEIR LEARNING ACHIEVEMENT : A CORRELATION STUDY - Putri Chantika Herman; Lena Sastri; Absharini Kardena; Elsi Amiza (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Students in junior high school felt anxiety and were afraid in learning English, so that their grades was quite good. They felt afraid and anxious when they made mistakes in speaking English because they were laughed by their friends. Then, they had no experience an learning English in primary school. The aim of this study is to identify the correlation between students’ anxiety and their Learning Achievement. The design of this research was correlation design. The population of this research were 67 students’ of seventh-grade students at SMP N 6 Padang. This research used cluster random sampling the sample was 31 students. To get the data this research used a questionnaire and test. To measure students’ anxiety using a tool the Foreign Language Classroom Anxiety Scale (FLCAS). The data in this research were analyzed by using the Pearson Product Moment Correlation Coefficient with SPSS 20 programs. The research result showed that the Coefficient of Product Moment was-0,784. It meant, there was a negative correlation between students‘ anxiety and their learning achievement ∝ was 0.05, so sig 0.00 less than 0.05. Negative science shows a significant relationship in reverse if the anxiety value is high then the value is low and if the value is high then the anxiety is low. It could be concluded that Ho was rejected and Ha was accepted. So the implication is that if the anxiety is high then the student's score is low and vice versa if the anxiety is low then the score is high.